Gerakan Npc Pada Game Pengenalan Huruf Menggunakan Algoritma Dijkstra Dengan Perbedaan Ketinggian Pada Obstacle - Angga Junianto Sadewantoro (Melek IT : Information Technology Journal, 2019)
Game is a play used as a medium of entertainment or for learning. In the game certainly there is a character that can not be played but the role to continue the story in the game that is NPC (Non Player Character). From previous research with the theme of NPC movement using algorithm dijkstra in game introduction of letters there is a problem if the environment obtained there is obstacle or commonly called obstacle NPC can not do the next movement if there is obstacle with a certain height. From the problem then the author intends to develop to add NPC movements with actions can pass an obstacle with the provision that the NPC can jump if the obstacle height is ¼ of the height of the NPC. In managing the NPC movement to go to the target is usually often experienced constraints as if there are various kinds of obstacles that exist around the environment sometimes NPC is difficult to determine the movement to be done. Pathfinding is a very supportive method to ease the NPC movement in finding the main target. The pathfinding accompanied by the dijkstra algorithm is perfect for giving Artificial Intelligence to the NPC. Calculate the exact algorithm with the whole area to find the closest distance to the target.